2006
DOI: 10.1083/jcb.200604123
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic cortical neural stem cells migrate ventrally and persist as postnatal striatal stem cells

Abstract: Embryonic cortical neural stem cells apparently have a transient existence, as they do not persist in the adult cortex. We sought to determine the fate of embryonic cortical stem cells by following Emx1IREScre; LacZ/EGFP double-transgenic murine cells from midgestation into adulthood. Lineage tracing in combination with direct cell labeling and time-lapse video microscopy demonstrated that Emx1-lineage embryonic cortical stem cells migrate ventrally into the striatal germinal zone (GZ) perinatally and intermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 43 publications
(75 reference statements)
5
69
0
Order By: Relevance
“…In vivo fate mapping of the dorsal Emx1 lineage found some olfactory bulb cells, although these were not further described in terms of GABAergic expression (Gorski et al, 2002;Willaime-Morawek et al, 2006). In addition, Willaime-Morawek et al (2006) found that Emx1-derived stem cells migrate from dorsal to ventral regions and generate striatal interneurons, further bolstering the idea of an expanded capability of dorsal cells.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…In vivo fate mapping of the dorsal Emx1 lineage found some olfactory bulb cells, although these were not further described in terms of GABAergic expression (Gorski et al, 2002;Willaime-Morawek et al, 2006). In addition, Willaime-Morawek et al (2006) found that Emx1-derived stem cells migrate from dorsal to ventral regions and generate striatal interneurons, further bolstering the idea of an expanded capability of dorsal cells.…”
Section: Introductionmentioning
confidence: 63%
“…Whether diffusible factors important for the postnatal neurogenic niche, such as sonic hedgehog, are present in different levels along the dorsoventral axis is unclear. Willaime-Morawek et al (2006) document dorsal Emx1 derived cells migrating to more ventral regions of the SVZ, presumably where they are exposed to the ventral environment and gain competence to generate striatal interneurons. In contrast to their findings, we report that the astrocytic progeny of dorsal radial glia that come to reside at the SVZ border remain in register with their radial glial precursors, apparently not mixing with ventral cells or migrating extensively in a dorsoventral direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are certain somatic stem cell populations that might reasonably be considered stationary (e.g. gut epithelial stem cells) and are dependent on highly localized signaling from the niche (e.g., review S. Takashima and V. Hartenstein) [14], whereas others may have limited migratory behavior, such as cortical neural stem cells migrating ventrally to the subventricular zone along the lateral wall of the striatum [15]. Still, other examples of more dramatic migratory capacity come from studies of the hematopoietic stem cells that move throughout the circulatory system and lodge themselves into different tissues (e.g., review by W. Lensch) [16].…”
Section: Introductionmentioning
confidence: 99%